Load shedding scheme based on frequency and voltage stability for an islanding operation of a distribution network connected to mini-hydro generation - Norazliani, Md Sapari; Hazlie, Mokhlis; Javed, Ahmed Laghari; Halim, Abu Bakar; Hasmaini, Mohamad; Mohd Rohaimi, Mohd Dahalan (Turkiye Klinikleri Journal of Medical Sciences, 2016)
This paper presents a load shedding scheme (LSS) based on system frequency and voltage stability (VS). In the proposed scheme, the amount of power imbalance is determined using a rate of change of frequency, and the load shedding priority is carried out based on a VS index. The load with the highest tendency for voltage collapse (based on the index value) is given first priority to be shed. Thus, by shedding the most sensitive load, the distribution system can be saved from power collapse and then the system can return to its nominal state after load shedding. The proposed LSS is validated through simulation using PSCAD/EMTDC software on a Malaysian distribution network that consists of two mini-hydro generators. The simulation results show that the proposed scheme manages to shed the optimal amount of load when compared to conventional and adaptive frequency LSS. Moreover, apart from frequency stability, the proposed scheme also shows a significant improvement in the voltage profile of the islanded system.